A Botanical Product Containing Cistanche and Ginkgo Extracts Potentially Improves Chronic Fatigue Syndrome Symptoms in Adults: A Randomized, Double-Blind, and Placebo-Controlled Study - Kan, Juntao; Cheng, Junrui; Hu, Chun; Chen, Liang; Liu, Siyu; Venzon, Dawna; Murray, Mary; Li, Shuguang; Du, Jun (Frontiers in Nutrition, 2021)
Dietary therapy may be beneficial in alleviating symptoms of chronic fatigue syndrome (CFS), a disorder that is characterized by extreme fatigue and other symptoms, but the cause of which remains unclear. The aim of this study was to evaluate the protective effect of a botanical product containing cistanche (Cistanche tubulosa [Schenk] Wight) and ginkgo (Ginkgo biloba L.) extracts on adults with CFS in a randomized, double-blind, placebo-controlled clinical trial. A total of 190 subjects (35–60 years old, non-obese) with CFS were randomized to receive one tablet of a low dose (120-mg ginkgo and 300-mg cistanche), a high dose (180-mg ginkgo and 450-mg cistanche) or a placebo once daily for 60 days. Blood samples and responses on the Chalder fatigue scale (CFQ 11), the World Health Organization’s quality of life questionnaire (WHOQOL), and the sexual life quality questionnaire (SLQQ) were collected at baseline and post-intervention. CFS symptoms of impaired memory or concentration, physical fatigue, unrefreshing sleep, and post-exertional malaise were significantly improved (p < 0.001) in both of the treatment groups. The botanical intervention significantly decreased physical and mental fatigue scores of CFQ 11 and improved the WHOQOL and SLQQ scores of the subjects (p < 0.01). Levels of blood ammonia and lactic acid in the treatment groups were significantly lower than those of the placebo group (low-dose: p < 0.05; high-dose: p < 0.01). In addition, the change in lactic acid concentration was negatively associated with the severity of CFS symptoms (p = 0.0108) and was correlated with the change in total physical fatigue score of the CFQ (p = 0.0302). Considering the trivial effect size, the results may lack clinical significance. In conclusion, this botanical product showed promising effects in ameliorating the symptoms of CFS. Clinical trials with improved assessment tools, an expanded sample size, and an extended follow-up period are warranted to further validate the findings.